Crack path predictions and experiments in plane structures considering anisotropic properties and material interfaces - P.O. Judt; A. Ricoeur (Fracture and Structural Integrity)
In many engineering applications special requirements are directed to a material's fracture behavior and the prediction of crack paths. Especially if the material exhibits anisotropic elastic properties or fracture toughnesses, e.g. in textured or composite materials, the simulation of crack paths is challenging. Here, the application of path independent interaction integrals (I-integrals), J-, L- and M-integrals is beneficial for an accurate crack tip loading analysis. Numerical tools for the calculation of loading quantities using these path-invariant integrals are implemented into the commercial finite element (FE)-code ABAQUS. Global approaches of the integrals are convenient considering crack tips approaching other crack faces, internal boundaries or material interfaces. Curved crack faces require special treatment with respect to integration contours. Numerical crack paths are predicted based on FE calculations of the boundary value problem in connection with an intelligent adaptive re-meshing algorithm. Considering fracture toughness anisotropy and accounting for inelastic effects due to small plastic zones in the crack tip region, the numerically predicted crack paths of different types of specimens with material interfaces and internal boundaries are compared to subcritically grown paths obtained from experiments.